Disseminated Mycobacterium haemophilum skeletal disease in a patient with interferon‐gamma deficiency. Issue 10 (October 2015) - Otome, O.; O'Reilly, M.; Lim, L.
Abstract Disseminated non‐tuberculous mycobacterial (NTM) infection is rare in immunocompetent adults. Anti‐interferon‐gamma (IFN‐γ) autoantibodies have recently been associated with NTM infections, particularly in patients of Asian ethnicity. We describe a case of disseminated Mycobacterium haemophilum skeletal infection due to anti IFN‐γ autoantibodies in a 71‐year‐old Cambodian man. He responded to a combination of anti‐mycobacterial antibiotics without requirement for immunomodulator therapy. Testing for acquired IFN‐γ deficiency due to IFN‐γ autoantibodies should be considered when standard tests for immunodeficiency are negative in patients with unusual or severe opportunistic infections, including NTM.